Primary hyperaldosteronism (Conn syndrome): MR imaging findings. - Sohaib, SA; Peppercorn, P; Allan, C; Monson, J; Grossman, AB; Besser, G; Reznek, R (2000)
PURPOSE: To describe the magnetic resonance (MR) imaging features of the adrenal glands in primary hyperaldosteronism and assess MR imaging in the detection and characterization of aldosterone-producing adenoma (APA). MATERIALS AND METHODS: The authors retrospectively reviewed the cases of 20 patients (13 female and seven male patients; age range, 14-67 years; median age, 46 years) with primary hyperaldosteronism who underwent 1.5-T MR imaging between 1995 and 1998. All patients underwent transverse T1- and T2-weighted imaging, and chemical shift imaging was performed in 17 patients. Imaging results were correlated with findings at biochemical testing, venous sampling, or surgery. RESULTS: Among the 20 patients, 10 (50%) had APA and 10 (50%) bilateral adrenal hyperplasia (BAH). In the detection of APA, MR imaging had a sensitivity of 70%, specificity of 100%, and accuracy of 85%. APAs (mean size, 20 x 16 mm) were iso- or hypointense relative to the liver on T1-weighted images and slightly hyperintense on T2-weighted images. With chemical shift imaging, the signal intensity decreased on the out-of-phase images in six of seven (86%) patients with APA and in eight of nine (89%) patients with BAH. CONCLUSION: MR imaging has a high specificity in the detection of APA. As with nonhyperfunctioning adenoma, APA and BAH show evidence of intracellular lipid at chemical shift imaging.